Los estados desarrollistas en el este asiático: aportaciones institucionales y límites históricos - Fernando DE LA CRUZ PREGO (Revista Iberoamericana de Estudios de Desarrollo)
Developmental State conceptualization emerged during second half of the XX century as an explanative hypothesis for the fast growing economies in the Asian northeast. Institutional economic views attributed to state intervention the responsibility for successful industrial transformation in the region and highlighted the contribution of specific institutional public patterns as: bureaucratic quality and autonomy, public support for industrial conglomerates conditioned to competitiveness and productivity performance based incentives. In the other hand, historical views warned against exporting institutional successful models as they rest on space and time dimensions with a high degree of historic determinism